How are macronutrient intake, BMI, ethnicity, age, and gender related to the composition of unstimulated saliva? A case study. Issue 1 (1st October 2018) - Mosca, Ana Carolina; Stieger, Markus; Neyraud, Eric; Brignot, Hélène; van de Wiel, Anne; Chen, Jianshe
Abstract: This study investigated how macronutrient intake, BMI, ethnicity, age, and gender are related to the composition of unstimulated saliva. First, two groups of Caucasian, Dutch subjects varying in daily intake of carbohydrate, fat, and protein were selected. The daily intake of macronutrients differed by two‐ to threefold between the low ( n  = 14) and high ( n  = 16) macronutrient intake groups. The same subjects were divided into two groups based on BMI: normal weight ( n  = 14, 22.5 ± 2.0 kg/m 2 ) and overweight ( n  = 16, 28.1 ± 3.4 kg/m 2 ). Second, one group of Caucasian, Dutch ( n  = 15) and one group of Asian, Chinese ( n  = 15) subjects were selected. Unstimulated saliva was collected from all groups. Protein concentration, amylolytic activity, lipolytic activity, and saliva flow rate were determined. None of the salivary parameters varied according to macronutrient intake and BMI. An effect of ethnicity on protein concentration was observed ( p  < .01; η 2 = 0.142), with Asians having a 45% higher protein concentration in unstimulated saliva than Caucasians. Age had a significant effect on all salivary parameters. Protein concentration ( p  < .01; η 2 = 0.256), amylolytic activity ( p  < .01; η 2 = 0.234), and lipolytic activity ( p  < .05; η 2 = 0.207) increased with age, while saliva flow rate decreased ( p  < .01; η 2 = 0.262). Gender had a significant effect on saliva flow rate ( p  < .01; η 2 = 0.130), with male subjects having a 32% higher flow rate than females. Age was the factor that had the greatest impact on the characteristics of unstimulated saliva. As the modulation of saliva composition according to diet has been reported previously, the extent to which macronutrient intake can affect saliva composition needs to be further investigated. Practical applications: Saliva plays an important role in food oral processing. From the breakdown of food structures to the binding of flavor compounds and the formation of a swallowable bolus, saliva is essential for the perception and appreciation of foods. Identifying the factors that affect saliva composition is, therefore, necessary to understand the differences in eating behavior, food perception, and preference across different consumer groups. This article aims to highlight the importance of considering saliva variability when designing food products that meet the needs of specific consumer groups.